Ligation of huge spontaneous porto-systemic collaterals to avoid portal inflow steal in adult living donor liver transplantation: A case-report - Elshobary, Mohamed (Int J Surg Case Rep, 2017)
INTRODUCTION: In adult living donor liver transplantation (LDLT), maintenance of adequate portal inflow is essential for the graft regeneration. Portal inflow steal (PFS) may occur due to presence of huge spontaneous porto-systemic collaterals. A surgical procedure to increase the portal inflow is rarely necessary in adult LDLT. PRESENTATION: A 52 years male patient with end-stage liver disease due to chronic hepatitis C virus infection. Preoperative portography showed marked attenuated portal vein and its two main branches, patent tortuous splenic vein, multiple splenic hilar collaterals, and large lieno-renal collateral. He received a right hemi-liver graft from his nephew. Exploration revealed markedly cirrhotic liver, moderate splenomegaly with multiple collaterals and large lieno-renal collateral. Upon dissection of the hepato-duodenal ligament, a well-developed portal vein could be identified with a small mural thrombus. The recipient portal vein stump was anastomosed, in end to end fashion, to the graft portal vein. Doppler US showed reduced portal vein flow, so ligation of the huge lieno-renal collateral that allows steal of the portal inflow. After ligation of the lieno-renal collateral, improvement of the portal vein flow was observed in Doppler US. DISCUSSION: There is no accepted algorithm for managing spontaneous lieno-renal shunts before, during, or after liver transplantation, and evidence for efficacy of treatments remains limited. We report a case of surgical interruption of spontaneous huge porto-systemic collateral to prevent PFS during adult LDLT. CONCLUSION: Complete interruption of large collateral vessels might be needed as a part of adult LDLT procedure to avoid devastating postoperative PFS.